2003
DOI: 10.1152/ajpregu.00721.2001
|View full text |Cite
|
Sign up to set email alerts
|

Normal and glucocorticoid-induced development of the human small intestinal xenograft

Abstract: The aim of this study was to determine whether intestinal xenografts could recapitulate human in utero development by using disaccharidases as markers. Twenty-week-old fetal intestine was transplanted into immunocompromised mice and was followed. At 20-wk of gestation, the fetal human intestine was morphologically developed with high sucrase and trehalase but had low lactase activities. By 9-wk posttransplantation, jejunal xenografts were morphologically and functionally developed and were then monitored for ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…Briefly, fetal small intestine from 16-to 20-wk fetuses was transplanted s.c. into SCID mice and kept in a pathogen-free environment for 6 mo as previously reported (13). We have shown in several recent publications (16,17) that fetal tissue transplanted into SCID mice reepithelializes and matures in a manner similar to that in the intrauterine environment as determined by microvillous disaccharidases and other enzymes. Accordingly, when studied the xenograft small intestinal samples are as viable as intestinal biopsy samples.…”
Section: Reagentsmentioning
confidence: 65%
See 1 more Smart Citation
“…Briefly, fetal small intestine from 16-to 20-wk fetuses was transplanted s.c. into SCID mice and kept in a pathogen-free environment for 6 mo as previously reported (13). We have shown in several recent publications (16,17) that fetal tissue transplanted into SCID mice reepithelializes and matures in a manner similar to that in the intrauterine environment as determined by microvillous disaccharidases and other enzymes. Accordingly, when studied the xenograft small intestinal samples are as viable as intestinal biopsy samples.…”
Section: Reagentsmentioning
confidence: 65%
“…Once small intestinal loops of fetuses of gestational age 16 -20 wk are transplanted into the s.c. capsule, a reepithelialization occurs and they develop in a manner similar to that predicted for the third trimester of human gestation in utero (16,17). Fetal human xenografts can be isolated and exposed to CT and then used to measure cAMP accumulation.…”
Section: Discussionmentioning
confidence: 88%
“…We have attempted to define the mechanisms involved in excessive inflammation in premature infants by analyzing the expression of innate inflammatory genes using resected ileal mucosa from fetal intestine, noninflamed elective surgical specimens in older children, intestinal tissue from NEC patients, and established immature human enterocyte cell lines. These data suggest that the excessive intestinal inflammatory response occurring in the premature intestine (20,21,22), a hallmark of NEC, is due to a developmental immaturity of specific innate immune response genes (4,23).…”
mentioning
confidence: 89%
“…Sterilized food (rodent laboratory chow 5001, Ralston Purina, St. Louis, MO) and deionized water were provided ad libitum from the day of arrival until the completion of the experiments. Two-centimeter sections of fetal ileum, stripped of its mesentery, were implanted subcutaneously into 4-to 6-wk-old homozygous SCID mice as reported previously (21,22). Surgery and postsurgical care were monitored according to an approved animal protocol from the Research Animal Care Committee (protocol 2005-N-000040) of the MGH.…”
Section: Human Intestinal Modelsmentioning
confidence: 99%
“…For instance, adrenalectomy in rats during the weaning period impairs the mor phological development of the small intestine [48], while injection of cortisone or hydrocortisone to suckling rats increases the expres sion and activity of many small intestinal maturation markers [49 51]. The development of a human intestinal xenograft model demonstrated the responsiveness of the human small intestine to cortisone during the maturation period [52,53]. More recently, in vitro studies demonstrated the role of GCs in the maintenance of intestinal epithelial barrier integrity [54].…”
Section: Function and Roles Of Intestinal Gcsmentioning
confidence: 99%